STRATEGI SALURAN PEMASARAN PADA INDUSTRI BUKU DAN ALAT PERAGA PENDIDIKAN - Firman Bachtiar (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2017)
The general objective of this study was to determine: Is there influence between contractual agreement and distribution intensity. Is there influence between focus target and distribution intensity. Is there influence between coordination effort and distribution intensity. Is there influence between retailer investment and distribution intensity. Is there influence between support programs and distribution intensity Is there influence between region autonomy situation and distribution intensity. Primary data from 29 major companies in the publishing and education equipment market, with causal comparative method to identify independent variable to investigate dependent variable. The result of the study shows that there is influence between contractual agreement and distribution intensity, there is influence between focus target and distribution intensity, there is influence between coordination effort and distribution intensity, there is influence between retailer investment and distribution intensity, there is influence between support programs and distribution intensity, there is influence between region autonomy situation and distribution intensity. Key words : causal comparative method, focus target and distribution intensity